Magma Budget From Lava and Tephra Volumes Erupted During the 25-26 October 2013 Lava Fountain at Mt Etna - Andronico, Daniele; Behncke, Boris; De Beni, Emanuela; Cristaldi, Antonino; Scollo, Simona; Lopez, Manuela; Lo Castro, Maria D. (Frontiers in Earth Science, 2018)
Determining the volume of the various types of products of a highly frequent active volcano can be very difficult, especially if most of them are deposited on a growing volcanic cone. The New South-East Crater (NSEC) of Mt Etna, Italy, may be considered one of the best case studies because of tens of paroxysmal episodes which it produced in the last few years. On 25-26 October 2013, a lava fountain at the NSEC produced magma jets up to 500 m high, a maximum ~8 km high column, a multilobate lava flow field 1.3 to 1.5 km long, and almost 30 m of growth in height of the NSEC cone. Mapping of explosive and effusive deposits allowed us to calculate the total volume of erupted products, including lava flows, proximal and distal tephra fallout, and the amount of coarse pyroclastics on the cone. The estimation of the latter products was also confirmed subtracting digital elevation models (DEMs) obtained at different stages of the NSEC growth. Results show that the volume of tephra fallout away from the cone was only <5 % of the total erupted magma, while the total volume of pyroclasts (distal plus proximal fallout) is about a third of the lava volume. Our analysis suggests that, at least for the studied event, three fourth of the involved magma was already partially degassed and thus emitted as lava flows. Hence, the main distinctive character of lava fountains at Etna, i.e. formation of eruption column and propagation of tephra-laden volcanic plumes to tens of km away from the volcano, would not contribute significantly to the final budget of erupted magma of the 25-26 October 2013 eruption. We finally propose that the same magma dynamics probably occur also during most of the common lava fountain episodes.